Trust in Supervisor Mediator between Organizational Commitment and Commitment to Change - Hamidreza Oreyzi; Hajar Barati (مطالعات مدیریت بهبود و تحول, 2014)
Introduction : Trust is considered as an essential variable affecting organizational effectiveness which is known as trust level that employees have in their managers. It appears as if trust in supervisor has an essential role in making an effective means between organizational commitment and commitment to organizational change. Methodology: in the current research that was conducted on 225 employees of Electricity Distribution Company of north Isfahan, organizational commitment questionnaire of Baulfour and Wechsler (1996), commitment to organizational change questionnaire of Barati and Oreyzi (2012), and trust in supervisor questionnaire of MCAllister (1995) was used. Findings: results of the research showed that there existed direct and indirect relationship between organizational commitment (OC) and commitment to change (CTC) and bootstrapanalysis showed that this relationship is established through mediating role of trust in supervisor (TIS). Exchange dimension of OC and CTC was mediated by cognitive dimension of trust, identification dimension was mediated by affective component of trust and affiliation dimension was mediated by cognitive and affective components. Conclusion: it is suggested to managers and organizations to try to create trust in subordinates if they want to create organizational commitment and commitment to change.